Environmental & architectural phenomenology. Vol. 6, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1995)
Vol. 6, No. 2, Spring 1995 (includes “items of interest,” "citations received,” book review of Edward Casey's Getting Back into Place, and essays by R. Murray Schafer & Louise Chawla).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals